The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1105/tpc.16.00953
|View full text |Cite
|
Sign up to set email alerts
|

MYC2 Orchestrates a Hierarchical Transcriptional Cascade That Regulates Jasmonate-Mediated Plant Immunity in Tomato

Abstract: The hormone jasmonate (JA), which functions in plant immunity, regulates resistance to pathogen infection and insect attack through triggering genome-wide transcriptional reprogramming in plants. We show that the basic helix-loop-helix transcription factor (TF) MYC2 in tomato () acts downstream of the JA receptor to orchestrate JA-mediated activation of both the wounding and pathogen responses. Using chromatin immunoprecipitation sequencing (ChIP-seq) coupled with RNA sequencing (RNA-seq) assays, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
275
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(309 citation statements)
references
References 72 publications
20
275
1
1
Order By: Relevance
“…1c and Supplementary Table 4). MYCs initiate various feed forward loops that allow a rapid activation of the transcriptional JA response (Du et al, 2017, Liu et al, 2019). Our ChIP-seq approach revealed that besides the autoregulation of MYC2 and MYC3, they also regulate JA biosynthesis either indirectly through binding to the AP2-ERF transcription factor gene ORA47 (Chen et al, 2016a) or directly by targeting the JA biosynthesis genes LOX2 and AOS2 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c and Supplementary Table 4). MYCs initiate various feed forward loops that allow a rapid activation of the transcriptional JA response (Du et al, 2017, Liu et al, 2019). Our ChIP-seq approach revealed that besides the autoregulation of MYC2 and MYC3, they also regulate JA biosynthesis either indirectly through binding to the AP2-ERF transcription factor gene ORA47 (Chen et al, 2016a) or directly by targeting the JA biosynthesis genes LOX2 and AOS2 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This results in degradation of JAZ repressors and permits the activity of a master regulatory bHLH transcription factor MYC2, accompanied by MYC3, MYC4, MYC5 and numerous other transcription factors, all of which have distinct but overlapping roles in driving JA-responsive gene expression (Song et al, 2017, Schweizer et al, 2013b, Fernandez-Calvo et al, 2011, Lorenzo et al, 2004, Bao et al, 2019). The result is a cascade of JA-induced genome reprogramming to modulate plant behavior such as plant immune responses (Du et al, 2017, Hickman et al, 2017). However, our knowledge of the JA-responsive genome regulatory program and, more broadly, in the plants general response to environmental stimuli is limited currently by assessment of only one or a small number of components.…”
Section: Introductionmentioning
confidence: 99%
“…The JA signalling pathway plays a critical role in improving plant resistance to fungus, such as Botrytis cinerea , Alternaria brassicicola , Fusarium oxysporum and Plectosphaerella cucumerina (Du et al., ; Yan & Xie, ). If the JA pathway is blocked, endogenous jasmonate does not accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…The JA signalling pathway plays a critical role in improving plant resistance to fungus, such as Botrytis cinerea, Alternaria brassicicola, Fusarium oxysporum and Plectosphaerella cucumerina (Du et al, 2017;Yan & Xie, 2015 in both positive controls and in the BSMV:TaCOI1 group, the leaves were crinkled (Fig. S3).…”
Section: Early Response Is Important For Plant Resistancementioning
confidence: 99%
“…Although the function of AT3G19970 has not been fully characterised, GO terms have been associated with it via identification of functional gene modules 118 lycopersicum is Solyc02g020890 ( Supplementary Fig. 3t); Solyc02g020890 was among 4774 genes in tomato whose expression was significantly affected by application of methyl jasmonate 171 . Table 5).…”
Section: Candidates Found In F Mandshurica and Resistant Taxa In Secmentioning
confidence: 99%